Head, thoracic, abdominal, and vascular injuries - Oestern, H.-J (Hans-Jörg); Trentz, O.; Uranues, Selman (European manual of medicine., 2011)
There currently is a clear tendency to an increasing number of accidental injuries in elderly people, in sport injuries and car crashes also in countries which recently joined the European Union and candidates to join the European Union. Patients expect very good functional results even after serious injuries. But in contrast to this development, Trauma Surgery as an independent field, is not yet established in all European countries. Therefore, it seems mandatory to compile a book that covers the state-of-the-art in Trauma Surgery. The book also serves to harmonise the practice of Trauma Surgery.